2016
DOI: 10.1371/journal.pone.0147151
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Specific Signature in the Maternal Transcriptome Composition of Mature, Unfertilized Zebrafish Eggs

Abstract: Maternal mRNA present in mature oocytes plays an important role in the proper development of the early embryo. As the composition of the maternal transcriptome in general has been studied with pooled mature eggs, potential differences between individual eggs are unknown. Here we present a transcriptome study on individual zebrafish eggs from clutches of five mothers in which we focus on the differences in maternal mRNA abundance per gene between and within clutches. To minimize technical interference, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 57 publications
(70 reference statements)
5
39
0
Order By: Relevance
“…This observation suggests that interindividual differences between rainbow trout females from the winter broodstock had larger influence on the egg transcriptome and developmental ability than HHP treatment of the eggs. Similar has been observed in the zebrafish ( Danio rerio ) eggs where differences in the expression of maternal genes in eggs from different clutches reflected differences between mothers [ 25 ].…”
Section: Discussionsupporting
confidence: 60%
“…This observation suggests that interindividual differences between rainbow trout females from the winter broodstock had larger influence on the egg transcriptome and developmental ability than HHP treatment of the eggs. Similar has been observed in the zebrafish ( Danio rerio ) eggs where differences in the expression of maternal genes in eggs from different clutches reflected differences between mothers [ 25 ].…”
Section: Discussionsupporting
confidence: 60%
“…A recent paper demonstrated that the transcriptome in unfertilized zebrafish eggs from different mothers can be quite variable while it was more uniform within clutches, which suggests that mother-related differences in the transcriptome may potentially be associated with egg quality and subsequent development of the embryo[29]. To this end, we performed a couples analysis in which we compared clutches of eggs from 3 couples that consistently produced bad quality eggs to those that frequently gave good quality eggs in order to eliminate some of the environmental effects on maternal health and egg competence.…”
Section: Discussionmentioning
confidence: 99%
“…3B-D), was determined by calculating each possible ungapped and unidirectional alignment of 5 nt or longer of the ribosomal stretch with all available 5 ′ UTRs of zebrafish RNA transcripts using the BLAST package version 2.2.29. The 5 ′ UTRs were retrieved from Ensembl BioMart and, in order to be able to compare our results with the transcriptomics set of Rauwerda et al (2016), Ensembl release version 79 was used. For each 5…”
Section: S Sticky Regions Analysismentioning
confidence: 99%
“…Per gene, the counts were averaged and the ratio of the counts on the maternal-and somatic-type (ms-ratio) was calculated; ms-ratios in maternally expressed and nonexpressed genes were calculated using the set of expressed and nonexpressed genes from Rauwerda et al (2016). Overrepresentation of maternally expressed genes in the sets with ms-ratios smaller or larger than one was calculated with a Fisher's exact test implemented in the R stats package, while excluding genes with a ms-ratio of exactly one.…”
Section: S Sticky Regions Analysismentioning
confidence: 99%